The impact of ulinastatin in complex therapy on the incidence of early postoperative complications after coronary artery bypass grafting (CARDIOLOGY OF UZBEKISTAN, 2025)
Aim. To evaluate the effectiveness of ulinastatin as part of complex therapy in reducing the incidence of early postoperative complications in patients with multivessel coronary artery disease after CABG. Materials and methods. The study included 160 patients treated in the cardiac surgery intensive care unit. They were divided into a main group (80 patients, who underwent risk prediction using a multifactorial scale and received ulinastatin) and a control group (80 patients, who received standard treatment). Research methods comprised clinical observation, application of the prognostic risk assessment scale, laboratory determination of inflammatory markers, and statistical analysis using Student’s t-test, the Mann–Whitney test, and Pearson’s correlation. Results. In the main group, the incidence of hyperthermia and pneumonia was 50% and 10%, compared with 100% and 12.5% in the control group. ARDS and multiple organ failure were three times less frequent (1.25% vs. 3.75%), mediastinitis occurred in 1.25% vs. 3.75%, and postoperative wound infection in 3.75% vs. 6.25%. No lethal outcomes were recorded in the main group, whereas mortality in the control group reached 2.5%. Conclusion. The combined use of a multifactorial risk prediction scale and ulinastatin reduces the severity of systemic inflammatory response, lowers the frequency of early complications, and prevents mortality after CABG.